Literature Review: Risk Factors And Early Detection Of Preeclamsia In Women Pregnant - Puspitasari, Yenny; Budi Santoso; Nursalam; Agus Sulistyono (Universitas STRADA Indonesia, 2020)
Background: The high maternal mortality of 2015 is a big problem in Indonesia, which is 305 per 100,000 live births (Indonesian Population Profile Supas Result, 2015). The maternal mortality of 2010-2012 is due to an increase in preeclampsia, eclampsia and other factors, such as social problems, cultures, less education, to economic issues. Methods: The design of the research used is the study of libraries, articles gathered using search engines such as EBSCO, ScienceDirect, ProQuest and Elsevier. The article used in the study was published in 2010-2019. Result: Based on the article collected results that there are several factors related to the preeclampsia in pregnancy and the intervention phase should be done early. These factors are the age of mothers during pregnancy, praitas, double pregnancy, the history of hypertension in the family, preeclampsia history during previous pregnancies and obesity. The cause of the mother's death is actually preventable with an adequate ANC pregnancy test and early detection of the risk of pregnant women. Conclusion: The introduction of a complementary obstetrician is given to mothers at risk of preeclampsia during pregnancy. Further studies are advised to consider the effects on various variables by considering the random effects and changes in the model with the addition of contextual effects in the analysis.